Effect of surgical stress on Serum cholesterol level - Verma, LP; Dutt, Chandrakala; Dutt, R.D. (International Journal of Medical Research and Review, 2015)
Introduction: Stress in the Biological sense is the interaction between damage & defense. Anything that causes stress endangers life unless it is counteracted by adequate adoptive response. Conversely anything endangers life causes stress and adaptive responses. Adaptability and resistance to stress are fundamental requisites for life and very vital organ and function participate in them. Aims: To assess the preoperative value of serum cholesterol in different elective surgical operations. Methodology: In study 40 normal subjects were taken for serum cholesterol estimation. Serum cholesterol was estimated in 100 patients who were taken for various surgeries in respect of age, sex, and social status. The patients were categorized under three groups, group A - patient who underwent operation lasting for 1/2 an hour or less, group B - those with operations lasting between half an hour to 1½ hour, group C - operations lasting for more than 1½ hour. Results: Serum cholesterol value in normal healthy individuals was ranged from 124 to 240. Serum cholesterol level falls to its maximum on the first postoperative day in all cases of group A, B and C except 3 cases in group C in which maximum fall was observed on 3rd postoperative day. Conclusion: The more the surgical stress slower was the recovery.